Behavior And Feeding Habit of Dog Conch (Strombus turturella) in South Bangka Regency, Bangka Belitung Islands Province - Supratman, Okto; Syamsudin, Tati Suryati; Okto Supratman (El-Hayah : Jurnal Biologi, 2016)
Dog conch (Strombus turturella) is one of important sources of fishery commodities withÂ  high economic values in Bangka Belitung. The needs of Dog conch as consumption still depends on fishermen harvest since its aquaculture has not been cultured until now. This study aims at determining behavior and feeding habit of dog conch. The study was conducted in July 2014 to January 2015. The experiments passed some stages 1) samples was taken in the field by hand collecting, 2) the experiment of seagrass consumed preference, 3) feeding behavior, and 4) Analysis of the stomach contents. The results indicate dog conch does not consume seagrass immediately, but detritus and microalgae species of Thalassiosira sp., Synedra sp., Nitzschia sp., Navicula sp. Dog conch eats by put the probiosis of the shell, then it grinds sediment layer, seagrass leaves and shells of other individuals as source if food. Dog conch behavior from beginning toÂ  ending of the observation includes several stages: 1) Initial treatment actively foraging, 2) Individuals dog conch assembled or in pairs, 3) on the second day, the dog conch hoards himself on the base of the substrate and only elastic probiosis which occasionally appear occasionally at the substrate bottom.